2020
DOI: 10.1097/inf.0000000000002619
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and Neurodevelopmental Outcomes Following Linezolid for Coagulase-negative Staphylococcal Infection

Abstract: Background: Coagulase-negative staphylococci (CoNS) frequently causes late-onset sepsis in preterm infants. Vancomycin is the first-line therapy, but the emergence of reduced vancomycin-susceptibility strains has resulted in linezolid use, of which long-term safety in preterm infants is unknown. Objective: Evaluate the association between linezolid exposure and neurodevelopmental impairment (NDI) or death at 18–21 months of corrected age, in preterm inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
8
0
4
Order By: Relevance
“…Thanks to its wide bacterial spectrum, including Gram-positive bacteria and its excellent bioavailability, linezolid emerged in the early 2000s as a good alternative to vancomycin. In the speci c population of neonates, literature data dealing with linezolid pharmacology, safety, effectiveness and tolerance in neonates is exponential thus demonstrating its growing importance (6,8,9,13). In the study NICU, the rst use of this drug was reported in 2014 and then increased yearly, raising our concern and leading to this work.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to its wide bacterial spectrum, including Gram-positive bacteria and its excellent bioavailability, linezolid emerged in the early 2000s as a good alternative to vancomycin. In the speci c population of neonates, literature data dealing with linezolid pharmacology, safety, effectiveness and tolerance in neonates is exponential thus demonstrating its growing importance (6,8,9,13). In the study NICU, the rst use of this drug was reported in 2014 and then increased yearly, raising our concern and leading to this work.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to its wide bacterial spectrum, including Gram-positive bacteria and its excellent bioavailability, linezolid emerged in the early 2000s as a good alternative to vancomycin. In the specific population of neonates, literature data dealing with linezolid pharmacology, safety, effectiveness and tolerance in neonates is exponential thus demonstrating its growing importance [ 6 , 8 , 9 , 13 ]. In the study NICU, the first use of this drug was reported in 2014 and then increased yearly, raising our concern and leading to this work.…”
Section: Discussionmentioning
confidence: 99%
“…Es un AM de origen sintético derivado de las oxazolidinonas. Su mecanismo de acción está dado por la inhibición de la síntesis proteica, al fijarse al sitio P (23s) de la subunidad ribosomal 50S e impedir que se forme el complejo ribosoma-fMet-tRNA 74 . Su espectro de actividad es exclusivo para bacterias grampositivas, incluyendo a Enterococccus y Staphylococcus resistentes a vancomicina.…”
Section: Linezolidunclassified
“…En todos los casos, los valores regresan a la normalidad luego de suspender el fármaco [77][78][79] . También se han descrito neuropatías periféricas u ópticas en adultos y niños; generalmente ocurren después de una exposición prolongada a linezolid (≥ 28 días), aunque se reportó la producción de neuropatía óptica después de sólo 16 días de tratamiento en una mujer de 29 años 74 . La neurotoxicidad puede no desaparecer después de retirar el fármaco 74 .…”
Section: Linezolidunclassified